Educare: A Catalyst for Change - Sterling, Lauren; Peavey, Sheryl; Burke, Michael (Maine Policy Review, 2010)
Educare is a national model for providing center-based early childhood care and education, focused on improving student achievement for children growing up in poverty. The authors of this commentary describe development of Educare Central Maine in Waterville, scheduled to open in September 2010.
Keywords: Maine; Educare; early childhood education; child care